2012
DOI: 10.5194/hessd-9-5611-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model based on dimensional analysis for prediction of nitrogen and phosphorus concentration in the River Laborec

Abstract: The main aim of this paper is to develop a model for pollutant concentration prediction in a stream. The developed model that determines nitrogen and phosphorus concentrations in a river is based on a dimensional analysis. Applications of dimensional analysis to water quality modelling are presented, pointing out possibilities of applying this methodology in water quality research. We investigate how dimensional analysis can be applied to water quality modelling and which benefits it can bring to researche… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Some of those minor time gaps were covered with interpolated values, thus introducing some amount of uncertainty in model inputs. Average uncertainty in the prediction can be calculated using the following equation [ 56 ]: where: σ = average uncertainty percentage, n = number of data points, x = observed data points, and y = predicted data points…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of those minor time gaps were covered with interpolated values, thus introducing some amount of uncertainty in model inputs. Average uncertainty in the prediction can be calculated using the following equation [ 56 ]: where: σ = average uncertainty percentage, n = number of data points, x = observed data points, and y = predicted data points…”
Section: Discussionmentioning
confidence: 99%
“…Some of those minor time gaps were covered with interpolated values, thus introducing some amount of uncertainty in model inputs. Average uncertainty in the prediction can be calculated using the following equation [56]:…”
Section: Plos Onementioning
confidence: 99%
“…The goodness of fit of the models was evaluated by regression of observed versus predicted and scatter plot. Comparison of the results for both the models showed that the backpropagation model (R 2 = 0.94) predicted the results more precisely than the multiple regression model (R 2 = 0.85) Zele ňáková, Čarnogurská, Šlezingr and Słyś [90] predicted nitrogen and phosphorus concentrations in river Laborec in Slovakia, employing dimensional analysis method. They used Buckingham theorem to develop a prediction model utilizing important variables such as stream discharge, area of catchment, stream velocity, temperatures of air and water, and pollutant concentration.…”
Section: Nitrogen and Phosphorus Concentrationmentioning
confidence: 95%